2014
DOI: 10.3109/15412555.2014.922176
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Affects Health Status and Predicts Mortality Among Subjects with COPD: Report from the Population-Based OLIN COPD Study

Abstract: Fatigue and decreased health status were closely related among subjects with and without COPD. Not only physical health status, but also fatigue and mental health predicted mortality among subjects with COPD. Fatigue assessed by FACIT-F, can be a useful instrument of prognostic value in the care of subjects with COPD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(46 citation statements)
references
References 36 publications
4
41
0
1
Order By: Relevance
“…Low physical activity is a strong predictor of mortality in COPD [5], and according to a recent report from the Copenhagen City Heart study also changes in physical activity towards decreased physical activity is associated to mortality among subjects with COPD [17]. We have previously shown that fatigue, as well as reduced physical health score, is associated to mortality among subjects with COPD [55]. Taken together, these findings imply that it is important to encourage physical activity among subjects with COPD, and when initiating rehabilitation, addressing fatigue could be an important component of rehabilitation efforts.…”
Section: Variables Includedmentioning
confidence: 84%
“…Low physical activity is a strong predictor of mortality in COPD [5], and according to a recent report from the Copenhagen City Heart study also changes in physical activity towards decreased physical activity is associated to mortality among subjects with COPD [17]. We have previously shown that fatigue, as well as reduced physical health score, is associated to mortality among subjects with COPD [55]. Taken together, these findings imply that it is important to encourage physical activity among subjects with COPD, and when initiating rehabilitation, addressing fatigue could be an important component of rehabilitation efforts.…”
Section: Variables Includedmentioning
confidence: 84%
“…In addition, findings from a recent study suggest that fatigue has deleterious effects on patient's mental health and was associated with increased mortality in patients with COPD. 26 Taken together, these findings suggest that clinicians need to evaluate for fatigue on a routine basis.…”
Section: Common Symptoms In Copd Patientsmentioning
confidence: 95%
“…Additionally, fatigue was associated with worse prognosis in patients with heart failure [12], had negative impact on health status, function, and mortality in an elderly population [13], and predicted mortality in chronic obstructive lung disease [14]. In another study, low levels of fatigue independently predicted longer recurrence-free and overall survival from breast cancer, when controlling for biological factors [15].…”
Section: Introductionmentioning
confidence: 99%